(untitled) (Indonesian Economic Justice Review, 2025)
This paper explores Indonesia’s green economy policies, analyzing their potential to promote both environmental sustainability and economic justice. As a country highly vulnerable to the impacts of climate change and environmental degradation, Indonesia has increasingly embraced green economy initiatives, such as promoting renewable energy, sustainable agriculture, and eco-friendly industries. However, the question remains whether these policies contribute to economic justice by ensuring that marginalized communities, particularly in rural areas, benefit from the transition to a green economy. The paper examines how green policies have impacted economic opportunities, particularly for indigenous communities, small-scale farmers, and low-income urban populations. It assesses whether the green economy fosters inclusive development or whether it perpetuates inequalities by favoring wealthier segments of society, such as large corporations and urban elites, who have better access to green technologies and capital. The study critically analyzes the role of government and private sector initiatives in addressing the economic and social dimensions of sustainability, including the need for job creation, equitable access to green technologies, and protection of vulnerable populations from environmental harm. The paper concludes with policy recommendations aimed at ensuring that Indonesia’s green economy transition supports both environmental sustainability and social equity, with a focus on creating economic opportunities for disadvantaged communities.